PENGARUH MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN DEEP LEARNING MENGGUNAKAN E-LKPD BERBASIS BUDAYA MELAYU TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA - Antika, Lara; Izzati, Nur; Hilda Syani Putri, Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine whether there is an effect of the Problem-Based Learning model with the Deep Learning approach using E-LKPD based on Malay culture on students' mathematical representation abilities on rotation and dilation material in class XI of SMA Negeri 5 Tanjungpinang. This study is a quasi-experimental study with a pretest-posttest control group design. The study population was all class XI students of SMA Negeri 5 Tanjungpinang consisting of four classes, namely XI.1 to XI.4. The research sample was determined using a probability sampling technique with the cluster random sampling method, so that class XI.1 was obtained as the experimental class and class XI.4 as the control class. Data collection was carried out using a test instrument in the form of essay questions to measure students' mathematical representation abilities on rotation and dilation material. The results of hypothesis testing using the Independent Sample T-Test test show a Sig. (2-tailed) value of 0.045, after the value is divided by two, a significant value of 0.0225 is obtained, this value is smaller than the significance level used, namely 0.05. Therefore, H0 cannot be accepted, thus, it can be concluded that there is an influence of the Problem Based Learning model with the Deep Learning approach using E-LKPD based on Malay culture on students' mathematical representation abilities.